The Impact of Liver Abscesses on Performance and Carcass Traits in Beef Cattle: A Meta-Analysis Study - Torres, Rodrigo de Nazaré Santos [UNESP]; da Silva, David Attuy Vey; Chardulo, Luis Arthur Loyola [UNESP]; Baldassini, Welder Angelo [UNESP]; de Almeida, Rafael Assis Torres; Almeida, Marco Tulio Costa; Curi, Rogério Abdallah [UNESP]; Pereira, Guilherme Luis [UNESP]; Schoonmaker, Jon Patrick; Machado Neto, Otavio Rodrigues [UNESP] (MDPI, 2024)
The use of high-grain diets in feedlots is associated with the development of acidosis and ruminitis, which can lead to the occurrence of liver abscesses (LAs). However, the effect of LA on carcass traits is not well known. This study assessed the effects of LA on the performance and carcass traits of beef cattle. Nine peer-reviewed publications with forty-seven treatment means were included in the data set. The effects of the LA were evaluated by examining the weighted mean difference (WMD) between LA (animal with LA) and control treatment (animal without LA). Heterogeneity was explored by meta-regression, followed by a subgroup analysis of the scores and percentages of liver abscess and concentrate level in the feedlot diet. Animals affected by LA showed a reduction in dry matter intake (−1.03%) and feed efficiency (−1.82%). Animals with an LA score of “A” (one or two small abscesses) exhibited a decrease in carcass weight (WMD = 3.41 kg; p = 0.034) and ribeye area (WMD = −1.37 cm2; p = 0.019). When assessing the impact of LA on carcass traits, the most reliable finding indicates a 1.21% reduction in the ribeye area, with no adverse effects observed on subcutaneous fat thickness or the marbling score in the carcass.
Keywords: abscess; carcass; feed efficiency; feedlot; liver